O Jardim das Oito Virtudes: Chang Dai-chien e a pintura chinesa de paisagem - Fernandes Filho, Marco Antonio Baena [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
This dissertation proposes a critical introduction to the work of Chang Dai-chien, an important Chinese painter of the 20th century, who lived in Brazil between the 50s and 70s. The starting point of this study will be the artist's production related to landscape painting , maximum genre of the Chinese pictorial tradition and main subject of his work. The research is based on the specific bibliography on the subject and on the classics of Chinese aesthetic thought, associated with the observation of the artist's capital works and paintings consecrated in the history of Chinese art. Along this path, both concepts related to literature, poetry and other arts are explored, as well as the historical and social forces at work in the contexts linked to his trajectory. These references are necessary for an initial analysis of Chang's production, in which aesthetic transformations are observed that culminated in the development of an individual style, which assimilates trends associated with Western art to a strictly traditional Chinese elaboration. Started in his passage through Brazil and developed in the following years, in the United States and Taiwan, this language guaranteed the presence of his works in international museums and in the global art market, contributing to the dissemination and preservation of traditional Chinese painting in an multicultural artistic scenario.

A presente dissertação propõe uma introdução crítica à obra de Chang Dai-chien, importante pintor chinês do século XX, que viveu no Brasil entre as décadas de 50 e 70. O ponto de partida deste estudo será a produção do artista relacionada à pintura de paisagem, gênero máximo da tradição pictórica chinesa e principal assunto de sua obra. A pesquisa se apoia na bibliografia específica sobre o tema e nos clássicos do pensamento estético chinês, associados à observação das obras capitais do artista e de pinturas consagradas na história da arte chinesa. Nesse percurso, são explorados tanto os conceitos relacionados à literatura, à poesia e a outras artes, quanto as forças históricas e sociais atuantes nos contextos ligados à sua trajetória. Essas referências são necessárias para uma análise inicial da produção de Chang, na qual se observam transformações estéticas que culminaram no desenvolvimento de um estilo individual, que assimila tendências associadas à arte do Ocidente à uma elaboração rigorosamente tradicional chinesa. Iniciada em sua passagem pelo Brasil e desenvolvida nos anos seguintes, nos Estados Unidos e Taiwan, essa linguagem garantiu a presença de suas obras em museus internacionais e no mercado global de arte, contribuindo para a divulgação e preservação da pintura chinesa tradicional em um cenário artístico multicultural.
The Garden of Eight Virtues: Chang Dai-chien and Chinese landscape painting
Keywords: Chang Dai-Chien; Zhang Daqian; Chinese painting; Landscape painting; Chang Dai-Chien; Zhang Daqian; Pintura chinesa; Pintura de paisagem